Development of microsatellite markers for the Japanese endemic conifer Thuja standishii and transfer to other East Asian species - Worth, James R. P.; Chang, K. S.; Ha, Y.-H.; Qin, Aili (BMC research notes, 2019)
Objective Design polymorphic microsatellite loci that will be useful for studies of the genetic diversity, gene-flow and reproduction in the Japanese endemic conifer Thuja standishii and test the transferability of these loci to the two other East Asian species, T. sutchuenensis and T. koraiensis . Results Fifteen loci were developed which displayed 3 to 21 alleles per locus (average = 9.2) among 97 samples from three populations of T. standishii . Observed heterozygosity for all samples varied between 0.33 and 0.75 (average = 0.54) while expected heterozygosity values were higher with an average over the 15 loci of 0.62 (0.37–0.91). Low multi-locus probability of identity values (< 0.00002) indicate that these markers will be effective for identifying individuals derived from clonal reproduction. All 15 loci amplified in 13 samples of T. sutchuenensis , the sister species of T. standishii , with 1 to 11 alleles per locus (average = 4.33) while 13 loci amplified in four samples of the more distantly related T. koraiensis with 1 to 5 alleles per locus (average = 2.15).